Histopathology of the Clarion Cochlear Implant Electrode Positioner in a Human Subject - Seyyedi, M (2013)
A silastic electrode positioner was introduced by the Advanced Bionics Corporation in 1999 and it was designed to achieve a perimodiolar position of the stimulating electrode. The positioner was voluntarily recalled in the United States in July 2002 due to an apparent higher risk of bacterial meningitis in patients in whom the electrode positioner had been placed. A detailed histopathologic study of the positioner in the human has not previously been published. The histopathologic findings in a 74-year old woman who underwent bilateral cochlear implantation using the positioner are presented. Findings including a large track caused by the combined electrode and its positioner with considerable disruption of the basilar membrane and osseous spiral lamina. Although there was a fibrous sheath around the electrode and positioner at the cochleostomy in both ears, this fibrous sheath did not extend deeply into the cochlea except at the apical end of the electrode beyond the positioner. This resulted in a large fluid space around and between the positioner and electrode within the cochlea and presumably in fluid continuity with the CSF space. Possible clinical implications are discussed.